2014
DOI: 10.1093/ejo/cjt104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retinoic acid on proliferation and gene expression of cleft and non-cleft palatal keratinocytes

Abstract: Overall, RA similarly inhibits proliferation of palatal KCs from cleft and non-cleft subjects and reduces the expression of specific genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…While previous studies have shown the importance of neural crest cells in CL/P development (14), different tissue systems are expected to contribute to this complex disease. In particular, keratinocytes from patients with CL/P have recently been reported to display differentiation defects (48)(49)(50)(51). On the basis of the key observation that p63 + KLF4 establish enhancers to regulate keratinocyte-specific genes, including critical craniofacial genes (see fig.…”
Section: P63 Regulates Expression Of Critical Genes Associated With C...mentioning
confidence: 99%
“…While previous studies have shown the importance of neural crest cells in CL/P development (14), different tissue systems are expected to contribute to this complex disease. In particular, keratinocytes from patients with CL/P have recently been reported to display differentiation defects (48)(49)(50)(51). On the basis of the key observation that p63 + KLF4 establish enhancers to regulate keratinocyte-specific genes, including critical craniofacial genes (see fig.…”
Section: P63 Regulates Expression Of Critical Genes Associated With C...mentioning
confidence: 99%
“…Vitamin A is acquired through products such as meat, milk, eggs and carrots (Metzler and Sandell, 2016). Vitamin A deficiency (serum level < 0.70 µmol/L) is a public health concern in countries in Africa and South East Asia, and was associated with craniofacial malformations including CLP (WHO 4 ) (Ackermans et al, 2011;Mammadova et al, 2014;Metzler and Sandell, 2016;Williams and Bohnsack, 2019). Supplementation with vitamin A was associated with a lower cleft risk (OR = 0.48) (Johansen et al, 2008).…”
Section: Vitamin Amentioning
confidence: 99%
“…RA treatment of pregnant rats causes impaired shelf adhesion (Choi et al, 2011). Interestingly, RA treatment also decreases the proliferation of human palatal epithelial cells in vitro (Mammadova et al, 2014) as well as their differentiation (unpublished data). RA also increases apoptosis in the midline edge epithelium (Choi et al, 2011;Cuervo et al, 2002).…”
Section: Ra In the Development Of Craniofacial Structures: The Second...mentioning
confidence: 82%
“…RA downregulates the expression of p63 and its target genes GJB6 and DLX5 in human palatal keratinocytes (Mammadova et al, 2014).…”
Section: Ra Inhibits the Expression Of Sox9 Andmentioning
confidence: 99%
See 1 more Smart Citation